2019
DOI: 10.1016/j.ribaf.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Politically connected boards, ownership structure and credit risk: Evidence from Chinese commercial banks

Abstract: This study explores whether the nature of ownership may condition the extent and impact of political connections on credit risk decisions. We find politically connected boards to exert significant influence on credit risk. Further evidence shows that ownership type of the bank moderates the link between politically connected boards and credit risk. Specifically, state owned banks appear to be more susceptible to credit risk while independent directors in private banks tend to be effective monitors. Our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 77 publications
3
36
0
Order By: Relevance
“…Our literature review is based on prior studies conducted in developed countries like the US and UK. One of the prior studies suggests that the most significant factor in determining firm performance would be the firm size (Boateng et al, 2019). Wamba et al, (2017) reported that in China the firm's earnings increased by 10 % annually over the period [2001][2002][2003].…”
Section: Introductionmentioning
confidence: 99%
“…Our literature review is based on prior studies conducted in developed countries like the US and UK. One of the prior studies suggests that the most significant factor in determining firm performance would be the firm size (Boateng et al, 2019). Wamba et al, (2017) reported that in China the firm's earnings increased by 10 % annually over the period [2001][2002][2003].…”
Section: Introductionmentioning
confidence: 99%
“…These factors considered as control variables are crossfirm differences in leverage, firm size, firm age, growth, dispersion of forecast error, volatility, auditor's choice, and number of independent directors on the board. Highleverage firms are likely to exhibit high COE because the component of risk premium increases as the function of leverage (e.g., Boateng et al 2019;Dhaliwal et al 2011;Gode & Mohanram 2003;Javakhadze et al 2016;Upadhyay & Sriram 2011). For firm size and age, large and mature firms tend to follow more analysts and have high disclosure levels in bridging the gap of information between firms and investors.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the effects of systematic exchange of favours between firms and political directors, political influence may encourage rent-seeking activities that divert firm's resources and enable politicians to achieve political and social objectives (grabbing-hand effect) (Boateng et al 2019). As such, investors could also perceive investments in PCON firms as risky, and thus increases the systematic risk of financing costs (e.g., Al-Hadi et al 2017;Bliss & Gul 2012b;Houston et al 2014;Pham 2019;Tee 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We find two papers with opposite effects. Boateng et al (2019) find that, in China, boards that are politically connected, due to the appointment of the CEO by the government, implement policies favourable to the state that eventually increase the firm's credit risk. However, in an Italian context, Infante and Piazza (2014) show that the presence on the board of a member of a political body decreases credit risk in the form of lower cost of debt.…”
Section: Board/ceo Network and Political Connectionsmentioning
confidence: 97%
“…For the European context, Andries and Brown (2017) find that during the financial crisis, board independence decreased credit risk, while the effect is not significant for the rest of the period. Also, for Islamic Asian countries (Grassa, 2016) and China (Boateng et al, 2019) board independence is found to reduce credit risk. Thus, the benefits associated with higher monitoring in countries where shareholder entrenchment is higher outweigh the drawbacks.…”
Section: Board Independencementioning
confidence: 99%